2010
DOI: 10.1158/1055-9965.epi-09-0841
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Folate, Related Genetic Variants, and Colorectal Cancer Risk in EPIC

Abstract: Background: A potential dual role of folate in colorectal cancer (CRC) is currently subject to debate. We investigate the associations between plasma folate, several relevant folate-related polymorphisms, and CRC risk within the large European Prospective Investigation into Cancer and Nutrition cohort.Methods: In this nested case-control study, 1,367 incident CRC cases were matched to 2,325 controls for study center, age, and sex. Risk ratios (RR) were estimated with conditional logistic regression and adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 56 publications
(97 reference statements)
9
53
0
Order By: Relevance
“…There was a weak inverse association between dietary folate intake and colorectal cancer risk (14), and blood folate levels were inversely associated in some (15)(16)(17)(18), but not all (10,(19)(20)(21)(22)(23)(24) studies. Vitamin B12 status was not associated with colorectal cancer in the majority of the studies (21,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…There was a weak inverse association between dietary folate intake and colorectal cancer risk (14), and blood folate levels were inversely associated in some (15)(16)(17)(18), but not all (10,(19)(20)(21)(22)(23)(24) studies. Vitamin B12 status was not associated with colorectal cancer in the majority of the studies (21,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent of 60 minutes of exercise per day to be physically active; consume a plant-based diet comprising a variety of fruits and vegetables; choose unprocessed cereals and grains over processed products; limit the intake of red meat and salt; avoid or limit alcohol consumption, to meet nutritional needs without the use of food supplements [218] avoid energy-rich foods, sugary drinks, fast foods and processed meat, and genetically modified foods modified to increase certain types of cancer (such as colorectal cancer) by modification in the nucleic acids thus causing changes in enzymatic activity [219,220,223,224].…”
Section: Iii-2-9 Dietary Recommendationsmentioning
confidence: 99%
“…As usual in the case of such studies, it is difficult to obtain the same tendencies in the results. Both Collin et al [19] and Eussen et al [20] conducted meta-analyzes which showed no correlation between MTHFR gene polymorphism and the risk of cancer of the prostate, or rectum, respectively.…”
Section: Vitamin Chemoprevention?mentioning
confidence: 99%